ELABORASI KOGNITIF DALAM PROSES ABSTRAKSI KONSEP MATEMATIKA - Mandasari, Novianti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— This paper explains how the elaboration model that a student does in the abstraction process of mathematical concepts. Every mathematical activity undertaken by a student will not be separated from the concept of mathematics itself, learning mathematical concepts are being started from the things are abstract. abstract is something that is not form, something intangible. The word abstract is closely related to the word abstraction. Abstraction itself is an important component of mental activity that aims to formulate basic concepts of mathematics. In the process of learning basic concepts of mathematics that have been studied previously must be re-emerged in the memory of students. storage of information at any time, which involves coding, storing, and retrieving. In the process of encoding information of someone's ability to remember not only in-depth processing or meaningful, but someone can have a good memory when someone involves elaboration in the coding process Keywords— Cognitive Elaboration, Abstraction Process, Mathematical Concept Abstrak— Tulisan ini menjelaskan bagaimana model elaborasi yang dilakukan seorang siswa dalam proses abstraksi Konsep matematika. Setiap kegiatan matematika yang dilakukan seorang siswa tak akan terlepas dari konsep matematika itu sendiri, pembelajaran konsep matematika dimulai dari hal –hal yang bersifat abstrak. abstrak adalah sesuatu yang tidak berbentuk, sesuatu yang tidak berwujud. Kata abstrak sangat berkaitan erat dengan kata abstraksi. Abstraksi sendiri merupakan  kompenen penting dari aktivitas mental yang bertujuan untuk merumuskan konsep-konsep dasar materamatika. Dalam proses pembelajaran matematika konsep-konsep dasar yang telah dipelajari sebelumnya harus dimunculkan kembali dalam memori siswa. penyimpanan informasi di setiap waktu, yang melibatkan pengkodean, penyimpanan, dan pemanggilan kembali. Dalam proses pengkodeaan informasi kemampuan mengingat seseorang tidak hanya pada pemprosesan yang mendalam atau bermakna, tetapi seseorang dapat memiliki ingatan yang baik ketika seseorang tersebut melibatkan elaborasi dalam proses pengkodeannya. Kata Kunci— Elaborasi Kognitif, Proses Abstraksi, Konsep Matematika